2021
DOI: 10.2196/preprints.30422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in Stress Throughout Pregnancy and Postpartum Period During the COVID-19 Pandemic: Longitudinal Study Using Ecological Momentary Assessment and Data From the Postpartum Mothers Mobile Study (Preprint)

Abstract: BACKGROUND Stress has been associated with adverse birth and postpartum health outcomes. Few studies have explored racial differences in maternal stress in a birthing population longitudinally in the United States (U.S.) during the ongoing COVID-19 pandemic. OBJECTIVE This study aimed to: (1) assess changes in reported stress before, during, and after initial emergency declarations (e.g., stay-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The need for tailored digital supportive interventions for the postpartum period is greater than ever given the increasing rates of perinatal stress, depression, and substance use during the COVID-19 pandemic [ 162 ]. A growing number of studies have shown increases in postpartum anxiety and depression, perinatal stress, and difficulties with bonding and breastfeeding since the beginning of the pandemic [ 163 , 164 ], all of which significantly increase the risk for risky drinking. This increased risk is combined with the fact that women who use substances are less likely to receive postpartum care [ 165 ] and are more likely to report poor relationships with their health care providers and negative experiences seeking care [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for tailored digital supportive interventions for the postpartum period is greater than ever given the increasing rates of perinatal stress, depression, and substance use during the COVID-19 pandemic [ 162 ]. A growing number of studies have shown increases in postpartum anxiety and depression, perinatal stress, and difficulties with bonding and breastfeeding since the beginning of the pandemic [ 163 , 164 ], all of which significantly increase the risk for risky drinking. This increased risk is combined with the fact that women who use substances are less likely to receive postpartum care [ 165 ] and are more likely to report poor relationships with their health care providers and negative experiences seeking care [ 166 ].…”
Section: Discussionmentioning
confidence: 99%